Anxiety and Adaptation of Behavior in Pregnant Zhuang Women During the COVID-19 Pandemic: A Mixed-Mode Survey - Ge Y; Shi C; Wu B; Liu Y; Chen L; Deng Y (Dove Medical Press, 2021)
Yuan Ge,1 Chunhong Shi,2 Bin Wu,1 Yannan Liu,3 Ling Chen,1 Yuegui Deng4 1School of Nursing, Guangxi University of Chinese Medicine, Nanning, 530200, People’s Republic of China; 2School of Nursing, Xiangnan University, Chenzhou, 423000, People’s Republic of China; 3Nursing School, Hunan University of Medicine, Huaihua, 418000, People’s Republic of China; 4Nursing Department, The First Affiliated Hospital of Guangxi University of Chinese Medicine, Nanning, 530022, People’s Republic of ChinaCorrespondence: Chunhong ShiSchool of Nursing, Xiangnan University, 889 Chenzhou Avenue, Suxian District, Chenzhou, 423000, Hunan, People’s Republic of ChinaTel +86 15907354840Fax +86-735-2325007Email shichunhong@xnu.edu.cnPurpose: This study explored the impact of COVID-19 on the mental health and adaptation of behavior of Zhuang women in China to provide more specific guidance for the social and medical practice of pregnant women during public health emergencies.Participants and Methods: This cross-sectional study recruited 446 pregnant Zhuang women from obstetric outpatient clinics in four tertiary hospitals and online maternity schools in Nanning, Guangxi, between February 24 and March 1, 2020. Self-designed questionnaires and the Self-Rating Anxiety Scale were used.Results: During the COVID-19 pandemic, the prevalence rate of anxiety among women was 36.77%, and some adaptation of behavior was observed. Logistic regression analysis showed that pregnant women who had an annual household income of less than $7,000, were primiparous, went out for prenatal examination, wanted to self-monitor during pregnancy but did not know how to do it, believed that they should be strictly isolated at home and cancel prenatal examinations, and expected to receive pregnancy healthcare through teleconsultation services showed a higher risk of anxiety. Nevertheless, pregnant Zhuang women who were 22– 35 years old, undergraduate-educated, and in their second trimester were less likely to suffer from anxiety.Conclusion: The COVID-19 pandemic has a significant psychological impact on pregnant women from ethnic minorities. Factors related to quarantine and social isolation policies appear to drive changes in behaviors and anxiety disorders. Multidisciplinary mental health services and culturally sensitive interventions are necessary for minority pregnant women, especially for low-income primiparous women in the first or third trimester.Keywords: pregnant women, minority, psychological, behavior, coronavirus disease 2019